DIGITAL LIFESTYLE CENTER BSD BORED PILE FOUNDATION AND DIAPHRAGM WALL WITH GROUND ANCHOR DESIGN - PUTRI PAMBHARU (NIM: 15014072), ABHINAYA
Digital Lifestyle Center BSD is a 7-story building in BSD City, South Tangerang. This building consists of 7 floors that functioned as office, shopping center, and cinema. This building also has 2 basement floors and 1 semi-basement that functioned as parking area. This final project is focused on designing the geotechnical aspects such as foundation and retaining wall. The foundation system is chosen with consideration based on the existing soil condition and some applicable codes, resulting in 0.6 meter bored pile with a total of 132 pile caps. The depth of foundation consists of three different depth, 15 meter, 22 meter, and 23 meter, which depend on the upper structure loads. Lateral deformation, settlement, and axial capacity have shown that the design is egligible to the code design. Diaphragm wall is designed with ground anchor reinforcement to protect basement excavation. The designed diaphragm wall will use 3 different depth of penetrations, 21 meter, 20 meter, and 18 meter. The anchors required are 1 anchorage, 3 anchorages, and 2 anchorages with each ground anchor is assigned to different prestress force ranging from 200 kN to 500 kN. Excavation is analyzed with PLAXIS 2D. Deformation of the wall and stability have shown that the design of diaphragm wall is safe.